1987
DOI: 10.1152/ajpendo.1987.252.6.e734
|View full text |Cite
|
Sign up to set email alerts
|

Norepinephrine storage, distribution, and release in diabetic cardiomyopathy

Abstract: The ability of hearts to store, distribute, and release norepinephrine (NE) was investigated in rats 8 wk after the induction of diabetes by an injection of streptozotocin (65 mg/kg iv). Chronic diabetes was associated with increased content and concentration of NE in heart and in other tissues such as kidney, brain, and spleen. Reserpine or tyramine treatment resulted in depletion of endogenous cardiac NE in control and diabetic rats. The depletion of NE stores at different times after a dose of reserpine was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
56
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 2 publications
4
56
0
Order By: Relevance
“…Table 2 summarizes these changes. Increased levels of NA have been reported in many viscera 11,[24][25][26] in STZ diabetes, but there are not many studies that cover the time course of these experiments. 12 Some workers confine their studies of STZ diabetes to the first 8 weeks or so, and if the changes we report have a functional significance, it is unlikely that changes in function related to sympathetic nerve activity will be seen much before 8-10 weeks of hyperglycaemia have occurred.…”
Section: Discussionmentioning
confidence: 99%
“…Table 2 summarizes these changes. Increased levels of NA have been reported in many viscera 11,[24][25][26] in STZ diabetes, but there are not many studies that cover the time course of these experiments. 12 Some workers confine their studies of STZ diabetes to the first 8 weeks or so, and if the changes we report have a functional significance, it is unlikely that changes in function related to sympathetic nerve activity will be seen much before 8-10 weeks of hyperglycaemia have occurred.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, it has been demonstrated that cardiac noradrenaline content is increased in diabetic rats (31). In addition, it was reported that noradrenaline turnover, uptake, synthesis, and release are all enhanced in diabetic cardiomyopathy (32,33). Therefore, chronically high concentrations of noradrenaline in diabetes may contribute to the selective downregulation of ␤ 1 -ARs, as the affinity of noradrenaline is lower for ␤ 2 -ARs.…”
Section: Discussionmentioning
confidence: 99%
“…However, some investigators have reported increased cardiac norepinephrine uptake and increased cardiac sympathetic nerve activity in rats with STZ-induced DM. 50, 51 An increase in cardiac sympathetic activity accelerates MIBG turnover at nerve terminals, resulting in decreased cardiac MIBG accumulation in delayed images. However, the present study found the same cardiac MIBG WR in the rats, regardless of fluvastatin administration.…”
Section: Cardiac Mibg Accumulationmentioning
confidence: 99%